Gentamycin inhibition of KC1-induced contractions of myometrium isolated from non-pregnant and pregnant cows - Ocal, H; Yuksel, M; Ayar, A (Czech Academy Agricultural Sciences, 2004)
The aim of this study was to investigate the effects of gentamycin on KCl-induced contractions of myometrium isolated from both non-pregnant and pregnant cows. Myometrial strips were isolated from non-pregnant and pregnant cows and suspended in a jacketed organ bath filled with Krebs' solution at 37degreesC (pH 7.4) continuously bubbled with 95% oxygen and 5% carbon dioxide; isometric contractions were recorded using an isometric force displacement transducer. After manifestation of spontaneous contractions, KCl (60 mM) was applied to the bath and the effects of gentamycin (300 muM, 600 muM) on the amplitude (g) and frequency of KCl-induced contractions were evaluated in 10-minute intervals. Data were statistically analysed using Student's t-test and Wilcoxon signed-rank test. Gentamycin inhibited the frequency and amplitude of KCl-induced contractions in a concentration dependent manner. At 300 muM and 600 muM, gentamycin significantly inhibited the amplitude and reduced the frequency of contractions of myometrium isolated from both pregnant and non-pregnant cows. However, an increase in the extracellular Ca+ ion concentration virtually reversed this blockade. The results of this in vitro study indicate that gentamycin inhibits KCl-induced contractions of myometrium isolated from both non-pregnant and pregnant cows.
Keywords: gentamycin; myometrium; KCI; contraction; cow